Balancing growth and green the impact of economic growth financial development technological innovation and economic complexity on carbon neutrality in P5 Plus 1 nations - Sanjeet Singh; Pooja Bansal; Rami Owais; Mohd Shukri Ab Yajid; Sireesha Nanduri; Sandeep Sharma; A. Bhowmik; Jibitesh Kumar Panda (Discover Sustainability)
Abstract Addressing carbon emissions is an urgent priority for nations leading global economic and industrial activities. This study focuses on the P5 Plus 1 countries China, the United States, Russia, the United Kingdom, France, and Germany due to their dominant role in global carbon output and economic influence. The research investigates how four critical factors economic growth, development of the financial sector, technological innovation, and economic complexity affect efforts to reduce carbon emissions and achieve carbon neutrality. Using data spanning from 1995 to 2021, the study employs both advanced non-parametric and parametric statistical models to capture long-term patterns and causal relationships. The findings highlight that increasing economic complexity generally supports carbon reduction goals, though results differ by model. Technological innovation and financial development display both positive and negative impacts, suggesting context-specific effects, while economic growth continues to pose challenges to emission control. Based on these insights, the study recommends policies promoting clean technology development, green financial instruments, energy transition incentives, and sustainable industrial restructuring. These targeted strategies can help high-emission economies align their growth objectives with environmental sustainability goals.